A digital curation model for post-occupancy evaluation data. (4th March 2022) - Patlakas, Panagiotis; Musso, Marta; Larkham, Peter
ABSTRACT: Post-Occupancy Evaluation (POE) is an important component of a cyclical design process that allows cost savings and promotes accountability of designers, owners, and users, as well as allowing identification of facilities issues and informed decision-making. It is reasonable to expect that the combined effect of new data-gathering technologies and the increasing urgency of sustainable building design will be that POE studies will increase and, eventually, be applied at a mass scale. Digital Curation (DC) allows for the long-term preservation and constant re-use of research data. Yet there has been no attempt so far to develop a DC strategy for POE data. This paper introduces the concept of Digital Curation and relates it to objective, quantitative POE data. A combination of a literature review and a questionnaire sent to expert respondents is utilised in order to identify data types and major Digital Curation issues relevant to POE. A Digital Curation Model (DCM) for POE data is presented, drawing from the existing models, examples, and best practice available, intended to act as a framework that enables the storage, archiving, management, recovery and utilisation of such data on a mass scale. Finally, the importance, benefits, obstacles and implications of developing a suitable DC strategy for Post-Occupancy Evaluation are discussed.